A longitudinal investigation of early reading and language skills in children with poor reading comprehension. - Nation, K; Cocksey, J; Taylor, J; Bishop, D (2010)
BACKGROUND: Poor comprehenders have difficulty comprehending connected text, despite having age-appropriate levels of reading accuracy and fluency. We used a longitudinal design to examine earlier reading and language skills in children identified as poor comprehenders in mid-childhood. METHOD: Two hundred and forty-two children began the study at age 5. Further assessments of language and reading skill were made at 5.5, 6, 7 and 8 years. At age 8, fifteen children met criteria for being a poor comprehender and were compared to 15 control children both concurrently and prospectively. RESULTS: Poor comprehenders showed normal reading accuracy and fluency at all ages. Reading comprehension was poor at each time point and, notably, showed minimal increases in raw score between 6 and 8 years. Phonological skills were generally normal throughout, but mild impairments in expressive and receptive language, listening comprehension and grammatical understanding were seen at all ages. CONCLUSIONS: Children identified as poor comprehenders at 8 years showed the same reading profile throughout earlier development. Their difficulties with the non-phonological aspects of oral language were present at school entry and persisted through childhood, showing that the oral language weaknesses seen in poor comprehenders in mid-childhood are not a simple consequence of their reading comprehension impairment.